Green synthesis of khat mediated silver nanoparticles for efficient detection of mercury ions. (2021) - Tsegay, M.G; Gebretinsae, H.G.; Sackey, J.; Maaza, M.; Nuru, Z.Y.
Highlights: Silver nanoparticles were synthesized by green synthesis using Khat plant extract. Growth of Ag Nanoparticles is dependant on reaction time. Mercury heavy metal was detected by the green synthesized Ag nanoparticles. Abstract: A novel bio- synthesized Ag nanoparticles (AgNPs) using extracts from khat (Catha edulis) plant which is efficient towards mercury ion detection is reported. Ag NPs were characterized by HRTEM, EDS, FTIR/ATR, XRD, UV–Vis absorbance to investigate the size, morphology, chemical bonding, and optical properties, respectively. HRTEM analysis reveals spherical nanoparticles with an average particle size of 14.8 nm. EDS analysis reveals the presence of Ag on the samples and also week signals of Si, Cl, K, Ca, Fe elements originating from the khat plant. According to the FTIR/ATR analysis, we deduce that the phytochemicals in the khat plant are actively involved in the interaction and reduction of the Ag + ions to Ag. The Brag peaks identified on the XRD spectra are perfectly matched to Face-centered cubic Ag. The Ag NPs recorded a surface Plasmon resonance (SPR) at 450.279 nm which is responsible for the blue colour shift of mercury ion (Hg 2+ ) detection. As a direct application, the sensitivity of Ag NPs was tested towards mercury ions.